Enhancing innovation in livestock value chains through networks: Lessons from fodder innovation case studies in developing countries - Ayele, Seife; Duncan, Alan J.; Larbi, Asamoah; Truong Tan Khanh (Oxford University Press, 2012)
Fodder scarcity is a perennial problem for many smallholder farmers in developing countries. This paper discusses how fodder technologies and knowledge have been introduced and integrated in diverse livestock production systems in Ethiopia, Syria and Vietnam. A synthesis of lessons learnt shows that fodder innovation is triggered and diffused by actors interacting and learning in networks, and on farms. Fodder innovation, being only one element of livestock value chains, is sustainably enhanced when linked to other innovations and market-oriented activities that optimize productivity gains. Yet innovating smallholder farmers face systemic constraints to access markets, and need to organize in groups to exploit opportunities. The paper concludes that rather than treating innovation systems and value chain approaches to agricultural development as separate tools, the integration of their complementary features enhances smallholders’ innovation and market success.